Vyāsa and the Mahābhārata: Authorship, Interpretation, and the Multilayered Narrative - SHARMA, Deepti; RAGHAV, Priya (Anafora, 2024)
The Mahābhārata, an ancient and timeless Indian epic of great literary significance, has undergone a substantial transformation throughout its existence due to the intricate interplay among numerous authors, translations, and retellings. This research article delves into an in‐depth analysis of the intricate web of factors that have exerted influence on and brought about transformations in the interpretation of the Mahābhārata across diverse historical periods and within a multitude of cultural contexts. This paper aims to investigate the origins of the Mahābhārata and its early authorships. It will explore the diverse perspectives and interpretations that have contributed to the development of its intricate and multifaceted significance. This analysis places significant emphasis on the philosophical, moral, and sociopolitical aspects that are intricately interwoven within the epic. It aims to explore how these themes resonate with different historical periods and diverse audiences. This research study aims to explore the potential impacts associated with the translation and adaptation of the Mahābhārata into various languages. By examining the consequences of this process, the study seeks to shed light on the broader implications and outcomes that may arise from such linguistic transformations. The present research endeavors to investigate the influence of linguistic nuances, cultural disparities, and translational decisions on the formation of divergent interpretations and portrayals of individuals, occurrences, and ethical dilemmas. The translations of the epic have not only facilitated its wider dissemination, but they have also engendered further layers of significance and reinterpretation.